Making Lake Erie Smart by Driving Innovations in Technology and Networking - Pearson, Becky; Kearns, Tim; Slawecki, Tad; Stubbs, Bryan; Herzog, Max; Paige, Kelli; Fitch, David (Frontiers in Marine Science, 2019)
Tomorrow’s smart lake will able to predict what could happen and to identify actions that affect the trajectory of the lakes. Smart Lake Erie – the proof of concept – will integrate data from distributed sensors using resilient networks to feed adaptive, predictive analytics that define and perhaps even perform necessary management actions. This paper describes Smart Lake Erie pilot as a series of steps including convening innovation challenges, engaging stakeholders, securing the core observation system, and designing and operationalizing a sustainable Harmful Algae Bloom Early-Warning System. The technology platform of the pilot will be a window into what is needed to serve new contributors, new service providers, new stakeholders and consumers of the data and information service paradigm. Lessons learned are drawn from the early implementation of the pilot which are applicable to the larger Great Lakes region, other Region Associations within the U.S. Integrated Ocean Observing System, and the Global Ocean Observing System.